Optimization of Ideological and Political Education Courses for College Students and Strategies for Mental Health Education - Yao W (Psychology Research and Behavior Management, 2023)
Wendan Yao Section of Recruitment and Employment, Qiqihar University, Qiqihar, Heilongjiang, 161006, People’s Republic of ChinaCorrespondence: Wendan Yao, Email 02481@qqhru.edu.cnIntroduction: Most college students are still in the growth stage in the complex network environment. Therefore, it is necessary to consider measures for ideological education and psychological training.Methods: Firstly, by citing literature, this work explains the current network environment college students face and the adverse effects on their psychology. Secondly, the relationship between the ideological education work of college students and the network environment is expounded. Finally, the sampling survey method is adopted to analyze the use of the internet, information contact behavior, and the psychological status of college students at the present stage.Results: The results showed that: (1) those with a college degree or above accounted for 47.1%. The data show that college students are at the forefront of internet use. They bear more social responsibilities than other groups. (2) About 90% of people have different degrees of depression and anxiety.Discussions: The data show that psychological training and ideological and political education (IPE) for college students is necessary. This paper aims to sum up the obstacles existing in IPE and psychological training through the influence of network environment and bad information on IPE of college students. Based on the survey results, this paper can find a solution to create a good IPE environment for college students.Keywords: ideological and political education, network environment, mental health, curriculum optimization, sampling survey